Viewpoints on wind and air infiltration phenomena at buildings illustrated by field and model studies. (October 2015) - Sandberg, Mats; Mattsson, Magnus; Wigö, Hans; Hayati, Abolfazl; Claesson, Leif; Linden, Elisabet; Khan, Mubashar Ahmed
Abstract: Ventilation and infiltration caused by wind are difficult to predict because they are non-local phenomena: driving factors depend on the surrounding terrain and neighbouring buildings and on the building orientation with respect to the wind direction. Wind-driven flow through an opening is complex because wind can flow through the opening or around the building, in contrast to buoyancy driven flow. We explored wind and air infiltration phenomena in terms of pressure distributions on and around buildings, stagnation points, flow along façades, drag forces, and air flow through openings. Field trials were conducted at a 19th-century church, and wind tunnel tests were conducted using a 1:200 scale model of the church and other models with openings. The locations of stagnation points on the church model were determined using particle image velocimetry measurements. Multiple stagnation points occurred. The forces exerted on the church model by winds were measured using a load cell. The projected areas affected by winds in various directions were calculated using a CAD model of the church. A fairly large region of influence on the ground, caused by blockage of the wind, was revealed by testing the scale model in the wind tunnel and recording the static pressure on the ground at many points. The findings of this study are summarized as a number of steps that we suggest to be taken to improve the analysis of wind driven flow in buildings and with these suggestions as a basis for further improvement of prediction methods for wind-driven flows. Highlights: We analysed wind and air filtration phenomena at a 19th-century church. The number of stagnation points on the church model varied with the wind direction. Drag force was larger for higher numbers of stagnation points. Blockage of the wind caused a fairly large region of influence on the ground. The findings can be used to improve the prediction of wind-driven infiltration.